Agarose Spot as a Comparative Method for in situ Analysis of Simultaneous Chemotactic Responses to Multiple Chemokines - Ahmed, Mohaned; Basheer, Haneen A.; Ayuso, Jose M.; Ahmet, Djevdet; Mazzini, Marco; Patel, Roshan; Shnyder, Steven D.; Vinader, Victoria; Afarinkia, Kamyar (Scientific reports, 2017)
We describe a novel protocol to quantitatively and simultaneously compare the chemotactic responses of cells towards different chemokines. In this protocol, droplets of agarose gel containing different chemokines are applied onto the surface of a Petri dish, and then immersed under culture medium in which cells are suspended. As chemokine molecules diffuse away from the spot, a transient chemoattractant gradient is established across the spots. Cells expressing the corresponding cognate chemokine receptors migrate against this gradient by crawling under the agarose spots towards their centre. We show that this migration is chemokine-specific; meaning that only cells that express the cognate chemokine cell surface receptor, migrate under the spot containing its corresponding chemokine ligand. Furthermore, we show that migration under the agarose spot can be modulated by selective small molecule antagonists present in the cell culture medium.